In-vessel colorimetry of Wendelstein 7-X first wall components after OP2.1 - G. Motojima; S. Masuzaki; C.P. Dhard; D. Naujoks; Mattis Hänel; Yu Gao (Nuclear Materials and Energy)
Colorimetry has been continuously utilized for the estimation of deposition layer distribution on the first wall panels and divertor target elements in each Operation Phases (OP) of Wendelstein 7-X (W7-X). In OP2.1, significant achievements were made in plasma-wall interaction studies and divertor performance, completed by the installation of actively cooled divertors together with the change of material from fine grain graphite to Carbon Fiber-reinforced Composite. This upgrade enabled the achievement of long-duration plasma discharges, reaching up to 500 s with a total injected energy of 1.3 GJ. Compared to a factor of 2.5 increase in the net average deposition thickness between OP1.2a and 1.2b, no significant change was observed between OP1.2b and OP2.1. The balance of deposition and erosion of deposition layer on the first wall panels is presumably changed in OP2.1. The considerable reasons are discussed qualitatively from the point of possibilities such as lower surface temperature of the divertor target elements, lower impurity level of bulk plasmas, and difference of the location of sputtered carbon source. Moreover, the clear pattern of the colorimetry on the divertor target elements is seen in OP1.2a and OP2.1 not in OP1.2b. However, it is not currently conclusive whether changes in reflectivity and optical properties on the graphite divertor surface are due to erosion or deposition.